2011
DOI: 10.1111/j.1740-8709.2011.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Fortifying complementary foods with NaFeEDTA – considerations for developing countries

Abstract: As a highly bioavailable iron compound, sodium iron (iii) ethylenediaminetetraacetate (NaFeEDTA) has been recommended as a food additive for fortification. The amount of a food additive that can be ingested daily over a lifetime without appreciable health risk is termed the acceptable daily intake (ADI). The ADI for NaFeEDTA is based on body weight. For complementary foods and food supplements for infants and young children in low-income countries, where prevalence of underweight is high yet nutrient needs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Our baseline survey showed that there were 74.3% of elder infants and young children suffered from anemia. Based on our data at the monitoring time point at the six months, anemia prevalence was significantly decreased to near 30% through daily supplementation of complementary food supplements contained iron 5 mg/g, and this beneficial effect lasted during 18 month intervention, which indicated that food-based intervention would be an effective way to reduce anemia in children from 6 to 24 months of age [30], [31].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our baseline survey showed that there were 74.3% of elder infants and young children suffered from anemia. Based on our data at the monitoring time point at the six months, anemia prevalence was significantly decreased to near 30% through daily supplementation of complementary food supplements contained iron 5 mg/g, and this beneficial effect lasted during 18 month intervention, which indicated that food-based intervention would be an effective way to reduce anemia in children from 6 to 24 months of age [30], [31].…”
Section: Discussionmentioning
confidence: 80%
“…Because our current study is an observational study, probably the results can not directly demonstrate a causal link. However, such as complementary food supplements have been demonstrated effectively to improve nutritional status and elevate hemoglobin level in elder infants and young children [29]–[31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, NaFeEDTA has been added to the list of vitamin and mineral substances allowed as food additives in the EU (61). In areas with an underweight prevalence of~30%, 2 mg of iron as NaFeEDTA is suggested for children 6-24 mo of age (62). The need for legislation in countries such as Kenya is therefore evident to allow the use of NaFeEDTA in childrenÕs food, because its efficacy has been shown.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of wide approval, iron EDTA cannot be used in the required amounts in complementary foods for older infants and young children (6–24 months of age) because of concern about exceeding the maximum acceptable daily intake (ADI) of EDTA (Yang et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…The current maximum ADI of EDTA (JECFA ; JECFA ) allows a maximum daily dosage of 2–2.5 mg day −1 of iron as iron EDTA for infants and young children (Yang et al . ), whereas experts advocate that this amount should be two to four times higher (Rosenberg et al . ).…”
Section: Introductionmentioning
confidence: 99%